G316(P) A retrospective observational study of the inpatient management of children with severe acute malnutrition (SAM) in rural zambia. (24th May 2017) - Poffley, R; Henderson, L; Packer, S
Abstract : Aims: The inpatient management of children with complicated SAM is clinically challenging and mortality rates in Sub-Saharan African malnutrition units remain high despite the presence of WHO treatment guidelines. This study aims to describe the demographic and outcome characteristics of children admitted to a malnutrition unit over a 12 month period in rural Zambia and whether outcomes changed following the introduction of standardised treatment guidelines. Methods: A pre-post intervention design was used. A retrospective case note review was carried out of any child admitted to the paediatric ward from November 2015 – October 2016 who met the WHO criteria for SAM. The management of these children was compared with the WHO recommended ten steps for inpatient management. New treatment guidelines were introduced alongside teaching to medical and nursing staff in May 2016. Data were managed in MS Excel 2010 and analysed using Stata v13.1. Results: A total of 1930 children were admitted of which 177 (9.2%) had a diagnosis of SAM and remained inpatients for an average of 11 days. The mean age of children admitted with SAM was 26.9 months, 12.3% had HIV and 4.7% had malaria. The overall case fatality rate for the malnutrition unit was 20.9% and of the annual inpatient mortality SAM was a contributor in over a quarter (27%) of deaths. The most common cause of death was sepsis but dehydration was a concurrent diagnosis in 73%. Mortality rates were 23% pre-intervention and 15% post- intervention. When looking at 16 indicators of WHO guideline compliance it was found that only two indicators observed a significant change following intervention. Correct action for these indicators increased and related to iron supplementation (p=<0.001) and F75 volume (p=0.015). Conclusion: SAM is a significant cause of childhood inpatient mortality. This preliminary analysis identifies the management of sepsis and dehydration as key areas for further review in our study population. Treatment guidelines can improve compliance in some areas but other factors which influence concordance and the subsequent impact on outcome needs further exploration.